APAKAH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY BERPENGARUH TERHADAP PROFITABILITAS PERUSAHAAN LQ45? - Novia Eka Sariantono; Luh Putu Mahyuni (Universitas Pendidikan Nasional, 2019)
Do Good Corporate Governance and Corporate Social Responsibility Influence Profitability of LQ45 Listed Companies. This study aims to examine the influence of good corporate governance and corporate social responsibility on profitability of LQ45 listed companies in Indonesia Stock Exchange. The data analyzed were secondary data in the form of annual reports and sustainability report. The data were analyzed using multiple linear regression. The results of this research indicate: (1) Good corporate governance (GCG) has a significant effect on profitability of LQ45 listed companies; (2) Corporate social responsibility (CSR) does not have a significant effect on profitability of LQ45 listed companies. This research provides empirical evidence that implementation of GCG could influence profitability, while the implementation of CSR does not influence profitability. Keywords: Good corporate governance, corporate social responsibility, independent commissioner board, corporate social responsibility, disclosure index, return on equity